Nurturing Writing Proficiency through Theme-based Instruction - Osman, Siti Rafizah Fatimah; Ahmad, Erny Arniza; Jusoff, Kamaruzaman (2009)
This paper explores the effectiveness of theme-based instructional (TBI) method as a means of honing the writing skills and the motivation for writing of 36 pre-degree ESL learners in a Malaysian tertiary institution. The method which focused on development of language skills through discussion of themes provided the teacher a direct and effective way in guiding the learning processes the learners underwent in terms of how information was shared and kept and how the outcomes were ensued in pursuing writing. What surfaced as the semester progressed was that most learners had developed enthusiasm due to the empowerment entrusted to them and were more competent in writing due to the amount of research, reading, reviewing and conferencing they had done. Thus, this article discusses the concept of theme-based instruction and presents some remarks gathered from six selected students.